METODE MEMBACA KITAB KUNING ANTARA SANTRI DAN MAHASISWA - Mokhamad Miptakhul Ulum (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2018)
The kitab kuning is not a term because the book is yellow only, but is a book term written by ulama’. The kitab kuning is more familiarly spoken by Indonesian ulama even call it a kitab gundul (without a punctuation), but in academia both in Indonesia and overseas the kitab kuning is more popular as turats. Reading the kitab kuning is the ability that should be owned by every syariat seekers and the da’i candidates. The ability to read the kitab kuning gundul will be very helpful every muslim to explore the arguments of the al-Qur’an and al-Hadits. Santri and college student are science seeker whose success its is waiting by the community. They are trusted as the nation’s next generation who are able to transfer Islamic values. Santri has differences with college student in developing the ability to read the kitab kuning, but does not reduce the substance in understanding the contents of the kitab kuning. The method santri uses wetonan, sorogan, mużākarah and takhdim. While college student are use by qirā’ah, simā’ah, takallum and kitābah.